2008
DOI: 10.1242/dev.019802
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell flattening and junctional remodeling during squamous epithelial morphogenesis inDrosophila

Abstract: Diverse types of epithelial morphogenesis drive development. Similar cytoskeletal and cell adhesion machinery orchestrate these changes, but it is unclear how distinct tissue types are produced. Thus, it is important to define and compare different types of morphogenesis. We investigated cell flattening and elongation in the amnioserosa, a squamous epithelium formed at Drosophila gastrulation. Amnioserosa cells are initially columnar. Remarkably, they flatten and elongate autonomously by perpendicularly rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
99
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 44 publications
16
99
1
Order By: Relevance
“…We conclude that apical constriction-induced basal movement of cytoplasm and volume conservation are the key factors that control both cell lengthening and the nucleus movement. This mechanism differs from previously proposed mechanisms ascribing to microtubules a central role in controlling cell length in epithelial cells (18), fibroblasts (19), and myoblasts (17) as well as nucleus movement (20). Volume conservation seems to be an effective means for localized subcellular force-generating machineries to affect shape changes in much larger structures across entire cells and tissues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We conclude that apical constriction-induced basal movement of cytoplasm and volume conservation are the key factors that control both cell lengthening and the nucleus movement. This mechanism differs from previously proposed mechanisms ascribing to microtubules a central role in controlling cell length in epithelial cells (18), fibroblasts (19), and myoblasts (17) as well as nucleus movement (20). Volume conservation seems to be an effective means for localized subcellular force-generating machineries to affect shape changes in much larger structures across entire cells and tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…1C, Left). However, alternative scenarios seem plausible, in which separate, albeit sufficiently concerted, active cellular processes drive the sequence of apical and basal cell shape changes (16)(17)(18)(19) and the relocation of the nucleus (20,21) (Fig. 1C, Right).…”
mentioning
confidence: 99%
“…As depletion of PIP3 did not block actomyosin cable assembly, loss of Baz must also trigger a PIP3-independent pathway that drives cable assembly. Baz exhibits a reciprocal distribution to actomyosin in other processes in the Drosophila embryo, including germband extension and amnioserosa remodelling; however, the molecular basis of this reciprocal relationship is not well understood, although recent work has indicated that Rho-kinase is involved (Pope and Harris, 2008;Simões et al, 2010;Zallen and Wieschaus, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Apical constrictions of the amnioserosa also generate ratchet-like pulling forces on the actin cables of the lateral epidermis that move the epithelial sheets towards each other (Solon et al, 2009). The initially columnar amnioserosa cells flatten and elongate by reorienting their internal microtubules, and these dynamic cytoskeletally driven cell shape changes are crucial for the tissue closure process to proceed efficiently and smoothly (Pope and Harris, 2008). Interestingly, microtubules resist significant compressive forces in adult mammalian cells (Brangwynne et al, 2006), and by resisting actomyosin-based tensile forces via a tensegrity mechanism, they contribute to the control of the cytoskeletal prestress that maintains cell shape stability in embryonic and adult tissues and organs (reviewed by Ingber, 2006).…”
Section: Tissue Folding Invagination and Dorsal Closurementioning
confidence: 99%